ARBEKACIN – A RAY OF HOPE TO FIGHT AGAINST MDR AND XDR GRAM-NEGATIVE BACTERIA IN A SCIENTIFIC AND COST-EFFECTIVE WAY IN INDIAN SCENARIO - SARKAR, SOMA; SARKAR, DIPANKAR; NAMHATA, ANJUM; SENGUPTA, MANIDEEPA (Asian Journal of Pharmaceutical and Clinical Research, 2020)
Objective: The objective of the study was to see the in vitro activity of arbekacin, a novel aminoglycoside, against multidrug-resistant (MDR) and extensively drug-resistant (XDR) Gram-negative bacilli (GNB) so that it can become a good alternative as empirical treatment for severe sepsis. Methods: Identification and antibiotic sensitivity testing of the GNB isolated from the clinical samples were done using the VITEK-II system in a tertiary care hospital, Kolkata. MDR and XDR strains were selected by their definitions and molecular characterization was done by multiplex polymerase chain reaction. The minimum inhibitory concentration (MIC) value of arbekacin was detected by the E-test strip and compared with other aminoglycosides. Results: A total of 140 drug-resistant strains including ESBL- and carbapenemase-producing GNB were selected for the study. Arbekacin showed reduced values of MIC50 and MIC90 compared to other aminoglycosides for most of the drug-resistant GNB. Conclusion: Hence, in this drug-resistant era, arbekacin with the advantage of a single daily dose can be used as an empirical choice in severe sepsis as monotherapy or in combination with other antibiotics such as colistin or polymyxin to fight against MDR and XDR bugs.